Biomechanical parameters of gait among transtibial amputees: a review - Soares, Alex Sandra Oliveira de Cerqueira (2009)
Rehabilitation for lower-limb amputees needs to focus on restoration of daily functions and independent locomotion. As gait is reestablished, reorganization of the motor pattern takes place in order to optimize the functions of the locomotor system. Biomechanics is a field of study that enables understanding of this reorganization. From such knowledge, appropriate strategies for recovering the autonomy of the means of locomotion can be established. Thus, this paper had the aim of reviewing the current status of the biomechanics of locomotion among unilateral transtibial amputees. To achieve this aim, papers written in English or Portuguese and published up to 2005 were selected from the Cochrane Library, PubMed, Scientific Electronic Library Online (SciELO), Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs) and Dedalus databases. In cases of transtibial amputation, the absence of plantar flexors negatively affects locomotion. Increased absorption and energy generation by the muscles that control the hip joint of the amputated leg can be considered to be the main compensatory strategy developed by unilateral transtibial amputees during gait. Factors associated with the characteristics of the amputation, prosthesis and experimental protocol used directly influence the results.